A véretekkel lesz kifestve a házam - Surányi, Ádám (Hungary, 2011)
"My house will be painted with your blood!" follows events when extremist groups terrorizing the Roma residents of Gyöngyöspata village in March 2011 for several weeks, dressed in militia uniforms, claiming to keep order in the village.
Verzio Film Festival Submission
Keywords: Documentary films